Penyesuaian Diri Mahasiswa Palembang Pada Budaya Solo - Avirasari Abidin, Radha, Dr. Lisnawati Ruhaena, M.Si., Psikolog (2017)
The purpose of this study is to describe the Palembang student's self-adjustment to Solo culture. The character of the Palembang people who tend to be loud in speaking, less concerned about the surrounding, and less polite to the elderly. This is very reversed with the character of a solo person who is known to be more polite, and gentle he said. Based on the differences, the authors are interested to examine how Palembang students adjust to Solo culture so that needed a strategy that can ease the process of adjustment in the city of Solo. This research uses interview and observation method as data collection tool. Characteristics of this research subjects are Palembang students who run education in Solo, ages 18-23 years, 3 men and 3 women. The analysis used in this research is content analysis. The results of this study show that the adjustment description is adaptation, conformity, plan making, and individual differences. Adaptations, such as greeting each other, being hospitable, being nice and preferring to use Indonesian language in the communication process in order to avoid misunderstanding between individuals. Conformity, like sharing with friends, exchanging information, and performing common tasks. Create a savings-like plan that is used to purchase urgent needs. Individual differences such as respect for older people are indicated by the attitude of the body and the use of subtle language. Obstacles experienced by Palembang students such as obstacles in interaction, ethics, and language so as to reduce these barriers students will adjust to follow the rules that apply in the residence, respect the parents with bowing body, and use the Indonesian language in the communication process in order to avoid misunderstanding between individual. There is no specific difference between men and women. The conclusion of this study is that Palembang students can adjust to Solo culture, evidenced from the six informants have started to greet each other and respect the elder people. The implication of this research is that Palembang students can participate in socializing activities held in the community to better memahahi Solo people and reduce the difficulties experienced by students of Palembang.